Relationship between oral health and diabetes mellitus in maintenance hemodialysis patients - LIU Tao; YUAN Hui-zhong; LU Jin-lian; LI Gen (Linchuang shenzangbing zazhi)
Objective To investigate oral health in the maintenance hemodialysis（MHD） patients with type 2 diabetes mellitus,and understand the relationship between oral health and type 2 diabetes mellitus and the clinical significance.Methods Eighty-five patients subject to MHD in Huangshi Second Hospital were divided into two groups:diabetes group（19 patients） and non-diabetes group（66 patients）.The patient’s name,gender,age,duration of dialysis,dialysis frequency,relevant medical history and the primary disease causing chronic renal failure,smoking history,current heart failure,hypertension,BMI,FPG,HbAlc and h-CRP were recorded.The oral examination for MHD patients was performed,and the data of the decay teeth（D）,missing teeth（M）,filled teeth（F）,DMF teeth（DMFT）,debris index（DI）,calculus index（CI）,periodontal disease index（PDI） were recorded and compared between the two groups.The factors influencing oral diseases（dental decay and periodontal disease） in MHD patients with type 2 diabetes mellitus were analyzed Results In diabetes group（n = 19） and non-diabetes group in = 66),prevalence rate of dental decay was 89.5%and 62.1%,D（3.58 ± 1.30） and（2.08 ± 1.76）,M（10.47 ± 3.27） and（6.81±1.63）,DMFT（15.00 ±3.83） and（10.78 ±2.02）,DI（3.42 ± 1.21） and（1.61 ±0.74）,CI（2.37±0.60） and(1.46 ± 0.78,PDI（5.37±1.67） and（3.28 ± 2.02）,respectively,significantly higher in diabetes group than in non-diabetes group（P<0.05）.Conclusions The oral health status of MHD patients with type 2 diabetes mellitus was in low-level.Diabetes mellitus may be one of the factors causing worse oral health status in MHD patients.